A produção do espaço em uma cidade universitária: o caso de Viçosa,MG - Leticia de Melo Honorio (2012)
The following university project studies the spacial particularity of Viçosa, MG. The city is located in the Zona da Mata region in the state of Minas Gerais, an area which is known for its economic stagnation, however, it differs from the cities around, due to its comerce withinthe city. Reflecting on its specializade function which is, a college town,Vicosa's total area is represented by the model we call "extremities point". The Main ideia of the studies is to show that the college town of Viçosa has its specific characteristics due to the college activies thatresults in a segregated urban area. Studying case by case, it was reveled that the urbanization process of this college town intented to contribuit to the urderstand how the Brazilian urbanization works, a process still in progress, Has particularities to be reveled. It also enforced the importancy of urban studies in median and small centers (university), at a time when, due to the power of the national educational governament, university campus and tecnology instituits are expanding to cities like this, all over Brazil.